A sex/age anomaly in thermal comfort observed in an office worker field study: A menopausal effect?. (21st August 2021) - Xiong, Jing; Carter, Sarah; Jay, Ollie; Arens, Edward; Zhang, Hui; Deuble, Max; de Dear, Richard
Abstract: In a field study conducted in office settings in Sydney, Australia, background survey and right ‐ here ‐ right ‐ now thermal comfort questionnaires were collected from a sample of office workers. Indoor environmental observations, including air temperature, mean radiant temperature, air velocity, and relative humidity, were also recorded and matched with each questionnaire according to the time and location. During exploratory data analyses, we observed that female subjects aged over 40 and 50 or younger registered significantly warmer sensations than other subjects, male and female, from other age ranges. To further explore this phenomenon, the sample of building occupants was classified into two groups—women of perimenopausal age (over 40 and 50 or younger) while the remaining respondents served as a reference group for comparison. Women in the perimenopausal age range demonstrated an increased perception of warmth ( p  < 0.01) and expressed thermal dissatisfaction more frequently ( p  < 0.01) than the reference group respondents who were exposed to the same indoor environmental conditions. Furthermore, women of perimenopausal age also expressed preference for cooler thermal environments, that is, lower air temperature ( p  < 0.01) and greater air movement ( p <0.01) than the reference group, and their thermal neutrality (ie, the room temperature corresponding to a neutral thermal sensation) was approximately 2°C cooler than that of the reference group (20.7°C vs 22.4°C). A potential physiological explanation for the distinct thermal perception of women aged over 40 and 50 or younger observed in this study could stem from menopausal symptoms—the presence of hot flushes and dysregulation of the thermoregulatory system.